Intracellular accumulation of bilirubin as a defense mechanism against increased oxidative stress - Zelenka, Jaroslav; Muchova, Lucie; Zelenkova, Miroslava; Vanova, Katerina; Vreman, Hendrik J; Wong, Ronald J; Vitek, Libor (Biochimie, 2012)
Antioxidant, anti-inflammatory and anti-atherogenic effects have been associated with elevations of unconjugated bilirubin (UCB) in serum and with the induction of heme oxygenase-1 (HO-1), the rate-limiting enzyme in UCB synthesis. The aim of this study was to investigate the intracellular metabolism and antioxidant properties of UCB in human hepatoblastoma HepG2 cells and tissues of Wistar rats exposed to oxidative stressors and lipopolysaccharide (LPS), respectively. Intracellular UCB concentrations in HepG2 cells correlated with its levels in culture media (p < 0.001) and diminished lipid peroxidation in a dose-dependent manner (p < 0.001). Moreover, induction of HO-1 with sodium arsenite led to 2.4-fold (p = 0.01) accumulation of intracellular UCB over basal level while sodium azide-derived oxidative stress resulted in a 60% drop (p < 0.001). This decrease was ameliorated by UCB elevation in media or by simultaneous induction of HO-1. In addition, hyperbilirubinemia and liver HO-1 induction in LPS-treated rats resulted in a 2-fold accumulation of tissue UCB (p = 0.01) associated with enhanced protection against lipid peroxidation (p = 0.02). In conclusion, hyperbilirubinemia and HO-1 induction associated with inflammation and oxidative stress increase intracellular concentrations of UCB, thus enhancing the protection of cellular lipids against peroxidation. Therefore, the previously reported protective effects of hyperbilirubinemia and HO-1 induction are at least in part due to intracellular accumulation of UCB.
Keywords: Rats; buňky Hep G2; Antioxidants; Heme Oxygenase-1; Methemalbumin; lidé; Lipopolysaccharides; Rats, Wistar; Hyperbilirubinemia; Oxidative Stress; Hep G2 Cells; Lipid Peroxidation; krysa rodu Rattus; hemoxygenasa-1; antioxidancia; hem; Enzyme Activation; arsenitany; methemalbumin; zvířata; Humans; lipopolysacharidy; Bilirubin; aktivace enzymů; Arsenites; hyperbilirubinemie; bilirubin; sloučeniny sodíku; potkani Wistar; oxidační stres; Sodium Compounds; Heme; peroxidace lipidů; Animals